Chemical injury induced by the use of topical imiquimod: case report - Morais, Anne Diollina Araújo; Sousa, Gabrielle Oliveira; Aguiar, Valdelya Nara Pereira; Chaves, Filipe Nobre; Sampieri, Marcelo Bonifácio da Silva; Oliveira, Denise Hélen Imaculada Pereira (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Chemical injury consists in damage caused by a substance when it comes into contact with living tissue. Certain drugs can cause this type of lesion in the oral mucosa. Imiquimod (INN) is an example. Erythema, edema, vesicles, erosions, ulcerations and inflammatory reactions are among the adverse effects associated with the use of INN. Nevertheless, since its effects disappear when terminating treatment, INN is still considered an essential drug in the treatment of condyloma acuminata, actinic cheilitis, superficial basal cell carcinoma and molluscum contagiosum. The objective of this work is to report a clinical case of a 34-year-old male patient presenting a symptomatic lesion on the lower and upper lip mucosa; while including a literature review on potential adverse effects when prescribing topical INN 5% for the oral mucosa.